LIVING HADITS DI JAMA’AH TABLIGH(Suatu Polarisasi dan Pemetaan Pemahaman Terhadap Hadits) - Ade Afriansyah (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
This paper aims to identify and analyze what kind of living hadith they do (jama'ah tabligh) and then make a pattern and mapping of it so that it can add to the scientific treasure for readers and alternatives to foster a spirit of togetherness in diversity in understanding Islamic science (creating an Islamic Moderation). Literature review (library research) is selected and used with phenomenalogical analysis whose data is obtained through scientific searches, then the results are presented descriptively-qualitatively. The results of the research are: polarization and mapping of such a thing, which is divided into 3 (three): a. The contents of the hadith are considered as something that is guided absolutely without any interpretation in the opinion of individual humans (especially Muslims) by exceeding or exceeding the original text of the hadith, unless there are other arguments that support it (al-Qur'an or other hadith); b. The contents of the hadith should absolutely be used as an ideology. The contents of the hadith should absolutely be used as an ideology in religion; c. The contents of the hadith should be represented or displayed in a real way, so that it does not seem that it is only limited to knowing and understanding without any evidence from the perpetrators (especially Muslims).